[tex]f(x)=\frac{x-8}{x+7} \\
g(x)=\frac{-7x-8}{x-1} \\ \\
f(g(x))=\frac{\frac{-7x-8}{x-1}-8}{\frac{-7x-8}{x-1}+7}=\frac{\frac{-7x-8}{x-1}-\frac{8(x-1)}{x-1}}{\frac{-7x-8}{x-1}+\frac{7(x-1)}{x-1}}=\frac{\frac{-7x-8}{x-1}-\frac{8x-8}{x-1}}{\frac{-7x-8}{x-1}+\frac{7x-7}{x-1}}=\frac{\frac{-7x-8-8x+8}{x-1}}{\frac{-7x-8+7x-7}{x-1}}= \\ =\frac{\frac{-13x}{x-1}}{\frac{-13}{x-1}}=\frac{-13x}{(x-1)} \times \frac{(x-1)}{-13}=x \\ \Downarrow \\ f(g(x))=x \\
\checkmark[/tex]
[tex]g(f(x))=\frac{-7(\frac{x-8}{x+7})-8}{\frac{x-8}{x+7}-1}=\frac{\frac{-7(x-8)}{x+7}-\frac{8(x+7)}{x+7}}{\frac{x-8}{x+7}-\frac{1(x+7)}{x+7}}=\frac{\frac{-7x+56}{x+7}-\frac{8x+56}{x+7}}{\frac{x-8}{x+7}-\frac{x+7}{x+7}}= \\
=\frac{\frac{-7x+56-8x-56}{x+7}}{\frac{x-8-x-7}{x+7}}=\frac{\frac{-15x}{x+7}}{\frac{-15}{x+7}}=\frac{-15x}{(x+7)} \times \frac{(x+7)}{-15}=x \\ \Downarrow \\ g(f(x))=x \\ \checkmark[/tex]